Ensino das operações aritméticas básicas: uma proposta didática orientada pela sequência fedathi - Marques, Elias Coutinho (Universidade Federal Rural do Semi-Árido, 2019)
This dissertation aims at elaborating a didactic proposal that tackles the basic arithmetic operations: sum and subtraction. The target public of the proposal consists of students of base level courses that form teachers for high-school levels. This research was developed from a bibliographical study of theoretical references of Mathematics Education and the elaborated proposal includes the usage of a historical mathematical instrument – the abacus – and it was oriented by the FEDATHI Sequence, a teaching methodology that aims at provoking a changing in the teacher’s attitude, in order to improve teaching quality, and it is structured in four phases: Attitude Taking, Maturation, Solution, and Proving. By working with the sum and subtraction operations, even with high-school students, we were able to observe that many of them knew how to solve these operations, but, in most of the cases, they solved them mechanically, based on some algorithm that was taught to them during Elementary School, and they were unable to explain why such operations were returned that way. Students of initial formation teaching courses for High School levels are potential teachers of initial levels of the Elementary School, which includes the teaching of such mathematical operations. We believe that by using proper tools and applying a more participative method, whose questionings, counter examples, as well as the valorisation of errors are used as learning tools, we might contribute to a better awareness of the importance of understanding the logic and operation of the sum and subtraction algorithms before using them and, mainly, before learning them
Keywords: Operações aritmética; Adição; Sequência FEDATHI; Ábaco; Basic arithmetic operations; Sum; Subtraction; FEDATHI sequence; Abacus; CIENCIAS EXATAS E DA TERRA::MATEMATICA